90.8k views
4 votes
6x - 12 = 2 (3x - 9) + 6

User Chrislusf
by
5.9k points

1 Answer

1 vote

Answer:

6x + -12 = 3x + 9

Reorder the terms:

-12 + 6x = 3x + 9

Reorder the terms:

-12 + 6x = 9 + 3x

Solving

-12 + 6x = 9 + 3x

Explanation:

12 + 6x = 9 + 3x

-12 + 6x = 9 + 3x

-12 + 6x + -3x = 9 + 3x + -3x

6x + -3x = 3x

-12 + 3x = 9 + 3x + -3x

3x + -3x = 0

-12 + 3x = 9 + 0

-12 + 3x = 9

-12 + 12 + 3x = 9 + 12

-12 + 12 = 0

0 + 3x = 9 + 12

3x = 9 + 12

9 + 12 = 21

3x = 21

Divide each side by 3

x = 7

User Harsha Hulageri
by
6.4k points